Hastags and Digital Mobilization Movements (DMO): Communication Network Analysis on #BubarkanPOLRI vs #Polripresisi Hastags on Twitter Social Media - Leo Nando Sastro; Daniel Susilo; Teguh Dwi Putranto (Jurnal Komunikasi Profesional, 2023)
This study examines the role of hastags (#BubarkanPOLRI) that first appeared during the Buaya vs Cicak incident where the KPK wiretapped case against the Kabareskrim Mabes Polri which was allegedly involved in disbursing funds from Bank Century customers. Hastag (#BubarkanPolri) Reappeared during the riots at the Kanjuruhan Malang stadium as quoted from the @akmalmarhali20 account "Tear gas shooting is one of the causes of dozens of deaths at Kanjuruhan stadium, STOP COMPETITION ON HUMANITARIAN GROUNDS #Jokowi #BubarkanPOLRI" and @chewulandari__ "Please have a tragedy in Malang to be resolved. Don't ask who's wrong anymore, but ask WHO IS LYING! 1 The police if they turn back the data attacking the community is easy, while the 1000 people shout the dakta is useless. Let alone #BubarkanPOLRI #UsutTuntasTragediKanjuruhan". As well as #polripresisi as a reaction that arises from the development of cases that tarnish the good name of the National Police. As quoted from the @PolsekSebbar account "West Sebatik Police personnel appeal to residents to continue to maintain kamtibmas if there is a problem immediately reported to the Police" and @PolsekLbkPakam "Lubuk Pakam Police SPKT service to the community who make Reports of Loss of Important Letters. Served humanistically, comfortably, and free of levies". This study aims to continue the previous research by comparing two different hastags, namely, #BubarkanPOLRI and #polripresisi to see if the difference in hashtags can have an impact on mobilization between the two fences. #Polripresisi able to create mobilization as measured by the number of network structures formed compared to #BubarkanPOLRI that tend to show the emotions of Twitter users about their dissatisfaction with the Polri as a State institution that should be able to protect and protect the community, of course, the goal is for the National Police to immediately fix themselves with all the dark records that already have, the analysis of this study shows how actors use hastags to get support among twitter users for United in upholding justice.